AI-Driven Drug Discovery: Accelerating Pharmaceutical Research Through Machine Learning - Brajesh Kumar , Keerthipati Kumar , L. Lavanya, D. Esther Rani, Saqib Qamar (Cuestiones de Fisioterapia, 2025)
Artificial Intelligence (AI) has emerged as a transformative force in drug discovery, offering unparalleledpotential to accelerate the pharmaceutical research pipeline. This study explores the application of AIdriven approaches across multiple facets of pharmaceutical development, from drug design to clinicaltrials and personalized medicine. We present a comprehensive analysis of AI’s impact on drug discovery,clinical trial optimization, and personalized treatment strategies, highlighting significantimprovements in prediction accuracy, patient recruitment efficiency, and treatment optimization.Our findings demonstrate that AI-driven models can enhance the design and synthesis of novel drugcompounds, improving specificity and efficacy while reducing the time and costs associated withpreclinical development.